Efficacy of intracanal biological and fiber posts in the rehabilitation of grossly mutilated primary incisors: a clinical study - Kansal, Vedant; Rana, Vivek; Srivastava, Nikhil; Kaushik, Noopur (International Journal Of Community Medicine And Public Health, 2022)
Background: The aim of this study was to assess the efficacy of conventional fiber posts with biological posts followed by strip crowns in the restoration of grossly mutilated primary anterior teeth. Methods: A total number of 10 patients with 20 grossly mutilated primary anterior teeth were selected. After pulpectomy, samples were randomly divided into 2 groups, group I and II, post space was prepared in both the groups, followed by placing conventional fiber posts and biological posts in group I and group II respectively. Finally, samples in both the groups were then restored with strip crowns. Patients were recalled for follow up examination at 3, 6 and 9 months intervals by an independent operator who was blinded about the procedure to assess longevity, gingival health, color change of crowns and parents’ acceptability of restorations. Results: After 9 months follow up period 100% of the biological posts survived while only 60% of the conventional fibre posts were able to survive (p>0.05). Only 20% of the cases in group I showed mild gingival inflammation around the post while no gingival inflammation was seen in group II. Non - significant results were found on comparing color change of crowns and parents acceptance at 6 months follow up. Conclusions: Both conventional fiber post and biological proved to be clinically successful in terms of their survival, gingival health, parents’ acceptability and color stability of crowns. Biological restorations proved to be a viable alternative for the restoration of grossly mutilated primary anterior in terms of longevity, gingival health, parents’ acceptability and color change of crown.